An Activity Theory analysis: reasons for undergraduate students' absenteeism at a South African university - Scheckle, Linda (South African Journal of Higher Education, 2016)
This study seeks to ascertain the extent of undergraduate student absenteeism, the reasons for its occurrence and the actions performed afterwards. Activity Theory is the theoretical framework against which reasons for absenteeism of students enrolled in 3 or 4 year degree programmes across degree levels in four faculties of a university are surveyed. A research sampling method is used whereby 696 of a potential 1428 students respond to a structured and semi-structured questionnaire requiring qualitative and quantitative responses. An interpretive paradigm is used for the analysis. The Activity System’s mediating elements comprising subjects, rules, community, division of labour, tools and objects capture the range of cumulative influences and their interdependency. As substantive theory, Allardt’s Sociological theory assesses well-being. The study finds that students’ absenteeism reflects challenges regarding existence needs, compromised learning quality and a risk to throughput. Consequently some `objects’ might need redefinement. Departmental and institutional strategies are recommended. (148 words). Keywords: absenteeism; activity system; activity theory; Engeström; mediating element; contradiction/s; well-being.